The Implementation of the Dengue Hemorrhagic Fever (DHF) Eradication Program - Rossa Anugerah Putri; Herniwanti Herniwanti; Aldiga Rienarti Abidin; Endang Purnawati Rahayu (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2024)
Billions of people living in wet tropical climates are at risk of suffering from Dengue Hemorrhagic Fever. In 2019, until mid-December throughout Indonesia, there were 71,668 people with dengue fever, and 641 of them died. Indragiri Hulu Regency is an area with a wet tropical climate and it becomes an endemic area Rengat District. This study aims to analyze of the implementation of the Dengue Hemorrhagic Fever eradication program. The type of research is analytical qualitative with case study design. The research informant technique used purposive sampling with 11 people. From the results of research and observations, it is shown that human resources are limited in facilities, not enough infrastructure is available, funds are still limited, from fogging carried out when cases occur, Eradication of Mosquito Nests. Dengue Hemorrhagic Fever is still not actively carried out by the community, abate powder is not evenly distributed to the community, Counseling that is still interested in carrying out Eradication of Mosquito Nests for Dengue Hemorrhagic Fever. Minimally carried out and public awareness about the condition of the environment around the community which is still not clean, causing the development of dengue mosquito larvae. It can be concluded that the Dengue Hemorrhagic Fever eradication program at the Sipayung Health Center still needs to be improved. It is expected to make program innovations to increase public interest in carrying out Eradication of Mosquito Nests for Dengue Hemorrhagic Fever.